Pelatihan penggunaan media pembelajaran interaktif Sistem Informasi Geografis mata pelajaran Pemrograman Web - Aris Sudianto; Imam Fathurrahman; Hamzan Ahmadi; Mahpuz Mahpuz; Muhamad Sadali; Indra Gunawan; Baiq Andriska Candra Permana; Muhammad Wasil; Lalu Kerta Wijaya; Suhartini Suhartini; Harianto Harianto (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2021)
Interactive learning media is one of the tools in the learning process. With interactive learning media, it will help students understand the learning material better, especially subjects that require practice to better understand the theory being taught. Web programming subjects in vocational schools are one of the subjects that have a lot of practicums. Therefore, to support the delivery of the subject matter, good interactive learning media are needed and are following the needs of students. This PKM aims to provide training on the use of web-based interactive learning media for Geographic Information Systems (GIS) that have been developed so that students understand more about designing web-based applications. This activity was carried out at SMKN 1 Selong, with 25 participants from the Software Engineering department. The activity lasted for 4 months. The method used is lectures and direct practice on WEB-based software engineering with lecturers from the Informatics Engineering study program, Hamzanwadi University. The material presented is in the form of steps to make simple software by utilizing existing technology and seeing some examples that have been prepared previously by the resource person to be used by students. For this method use a computer with a local network. The results of the activity show that students can master basic techniques for WEB-based software and students are also able to make simple WEB-based applications by applying the concept of good system analysis